Improved storage and distribution of water in multi-storeyed residential buildings in semi-urban communities of India. (2017) - Ravishankar, V.
The distribution of daily requirement of water in multi-storeyed semi-urban residential buildings in India involves pumping from the ground level to a reservoir at the top, and gravity feed to all levels below. String diagrams bring out the scope for reduction of unnecessary movement of water. A modified storage arrangement is proposed resulting in a small saving in energy required for water distribution, aggregating to a considerable amount for a locality over time, thus improving sustainability. The estimated savings reaches up to 25%-30% for buildings with four to six levels, increasing to 50% for high number of levels. Other benefits like metering, easy maintenance also could result. However, one of the problems involved in implementation is the higher initial costs involved in terms of foregone space occupied by the tanks at each level, and additional costs of storage tanks, which are key aspects in the economics of construction.